PENGARUH DIAPHRAGM BREATHING EXERCISE TERHADAP SESAK NAPAS PADA KLIEN PPOK - Retnani, Shelfi Dwi (LPPM STIKes Bahrul Ulum Jombang, 2019)
Dyspnea for COPD clients is a major problem requiring major help. Apart from disturbing the comfort, dyspnea can inhibit the activity of the client. It is important for nurses to innovate interventions in reducing dyspnea in COPD clients. This study aimed to determine the effect of diaphragmatic breathing exercises as one of the interventions to reduce dyspnea. This study used a quasi-experimental design with pre-test and post-test with a control group, 46 respondents were selected by consecutive sampling, consisting of 23 respondents in the treatment group and 23 respondents in the control group. The independent variable in this study was a diaphragmatic breathing exercise. The dependent variable is dyspnea. Data collection for variable dyspnea using the CAT scale. The statistical test used was Mann Whitney and Wilcoxon Sign Rank Test with significant α = 0.05. The results of this study indicate that intervention diaphragmatic breathing exercises can reduce dyspnea in COPD clients with ρ = 0,000. Intervention of diaphragmatic breathing exercises can reduce dyspnea in COPD clients by increasing the strength of the diaphragm muscles which are the main muscles of breathing. Further research requires pulmonary physiological examination (spirometry test) as one of the research variables.